FACTORS THAT INFLUENCE BREAST SELF-EXAMINATION BEHAVIOR (BSE) ON STUDENTS - Roudho Jannah (Universitas Karya Husada Semarang, 2024)
The highest incidence of cancer in women is breast cancer (22% of all new cancer cases in women in the world). One way to detect breast cancer early is to do a breast self-examination (BSE) regularly and correctly. The purpose of this study is to find out the factors that affect the behavior of students of the DIII Midwifery Study Program FIK Unipdu in carrying out BSE on a regular basis. The research method used is cross sectional. The population in the study was all students of the DIII Midwifery Study Program and the sample used was 34 students with sampling techniques using accidental sampling. The results showed that there was no relationship between age (p value 0.097), knowledge (p value 0.136), family history (p value 0.196), family support (p value 0.017) and information sources (p value 0.064) with students' BSE behavior. It is hoped that health workers or educational institutions will motivate students to do BSE regularly and correctly.